Energy Security International and Local Issues, Theoretical Perspectives, and Critical Energy Infrastructures - Gheorghe, Adrian; Muresan, Liviu; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
In terms of energy security the Black Sea region is important to Europe. Inevitably and for very good reasons, a lot of attention has been given to the existing and planned pipeline routes going around or across the Black Sea. Much less attention has been given to the development of the Black Sea energy market in its own right and to the potential advantages of coping with some current and future energy issues in a multilateral regional format rather than through individual action at national level. The present book addresses, in a comprehensive manner, the current problematic of energy security and goes beyond pipeline politics, without playing down their continued significance; it addresses some topical questions related to the sustainability and resilience of energy systems as applicable to the Black Sea region.
I.Diversity in Energy Security: An International Perspective. European Approach to Energy Security -- Lessons Learned for Regional and Global Energy Security.-The European Union and the Wider Black Sea Region: Interests, Challenges and Opportunities -- Considerations on Sustainable Development and Energy Security -- Issues of Energy Security in the Black Sea Region.-II. Theoretical Perspectives to Energy Security. Enlarging the Perspective: Energy Security via Equilibrium, Information and Computation. Models for Energy Gaming and Governance -- Stochastic Simulation of Critical Infrastructures for Electric Power Transmission.-Conversion of Renewables Kinetic Energy of Water: Synthesis, Theoretical Modeling, and Experimental Evaluation -- Modeling and Evaluation of Security of Energy Supply in Regional Environments.-Energy Security: A Problem of Complex Systems and Complex Situations -- Cybersecurity: Threat Identification, Risk and Vulnerability Assessment -- III. Critical Energy Infrastructures: Efficiency, Security, and Governance. Asset Critically in European Gas Pipeline Systems. Increasing Challenges for NATO, its Member States and Industrial Protection of Critical Energy Infrastructures -- Operational Analysis Support to Energy Security in South East Europe: A Bulgarian Academic Community Approach.-Energy Security for Industrial and Military Installations; Emergent Conditions that Influence the Strategic Selection of Technologies -- The Energy Incident Database -- An Energy Security Strategy for Romania: Promoting Energy Efficiency and Renewable Energy Sources.-.
Keywords: Economics; Renewable energy sources; Engineering economy; Sustainable development; Economic policy; Economics, Mathematical; Economics/Management Science; Game Theory/Mathematical Methods; Renewable and Green Energy; Sustainable Development; Energy Economics; Economic Policy